Early warning and monitoring of COVID-19 using the Baidu Search Index in China. Issue 5 (May 2022) - Zhou, Wanwan; Zhong, Lixian; Tang, Xiaofen; Huang, Tengda; Xie, Yihong
Highlights: "Influenza", "pneumonia"on December 2019 can be used in the early warning in Wuhan. "COVID-19", "SARS", "pneumonia"et al in Wuhan may implicatedthe further development. "Pneumonia", "coronavirus"and "masks"implicated the potential epidemic in China.